Use of combinatorial analysis for the study of new material for solar cells applications - Roncallo, Scilla; Karmimi, O.; Scragg, Jonathan J.; Lane, David W.; Painter, Jonathan (Cranfield University, 2009)
This paper presents a combinatorial method for the deposition and characterization of new metallic precursors for photovoltaic materials. Onedimensional thin film alloy “libraries” were electrodeposited on Mo-coated glass. The library elements were deposited in two consecutive baths and then heated in a reducing atmosphere to promote interdiffusion of the elements. At the end of this process, the libraries possessed a composition gradient along their lengths, with single elements at their two opposite ends and one or more alloys and/or a solid state solution in between. This continuous range of compositions can therefore be considered a collection of specific precursors that can be interrogated by examining their corresponding locations, with the crystallographic structure along the library changing in accordance with the phase diagram for the metals. The libraries were then sulphurised or selenised by heating in a sulphur-rich or selenium rich atmosphere; this converted the metallic precursors in a continuous range of materials, candidates for potential solar cells absorbers. The libraries were analysed by X-ray diffraction and energy dispersive X-ray spectrometry. The X-ray diffraction results show phase changes across the libraries, which can be correlated with the original precursor concentration at that particular po
Keywords: Solar cells; Photonics; Solar cells - Materials; Photovoltaics; Photovoltaic power generation